Effect of peak inspiratory pressure on the development of postoperative pulmonary complications in mechanically ventilated adult surgical patients: a systematic review protocol. (December 2016) - Wamsley, Chelsa; Missel, Donald
Abstract : Review question/objective: The objective is to identify the effect of peak inspiratory pressure on the development of postoperative pulmonary complications. More specifically, the objective is to identify the effect of maintaining intraoperative peak inspiratory pressure less than or equal to 30 cmH2 O compared with peak inspiratory pressure greater than 30 cmH2 O on the incidence of postoperative atelectasis, pneumonia and acute respiratory distress syndrome in mechanically ventilated adult surgical patients.